Characterization of environmental radiological parameters on dose coefficient - Realistic dosimetry compared with epidemiological dosimetry models - Amin Shahrokhi; Tibor kovács (Heliyon, 2023)
Radiation exposure due to all-natural sources amounts to about 2.4 mSv per year. However, this amount might be changed to over 3 mSv y−1 according to the recently introduced ICRP radon dose coefficient factor. Previously, the radon contribution to the total dose from natural sources was about 1.2 mSv y−1. However, after the latest introduced dose conversion factor by ICRP, this value could technically be increased to around 2 mSv y−1. This paper attempts to address the following questions: (i) whether reducing radon concentration to the recommended level could address concerns about radiation exposure in underground workplaces, and (ii) the effects of the difference between the epidemiological dosimetry models and realistic dose estimation. The actual dose conversion factor (DCF) was calculated using measured annual average unattached and equilibrium factors, ranging from 16 ± 9 to 25 ± 10 mSv·WLM−1. Then, the estimated inhalation dose, both from self-calculated DCF and the value reported by ICRP-137, was compared: 5.6 ± 0.7–7.6 ± 0.9 mSv y−1 and 3.3 ± 0.4–3.6 ± 0.5 mSv y−1, respectively. It can be observed that exposure to a radon concentration lower than the recommended level does not guarantee a lower dose than the recommended value. The estimated dose was at least two times greater than the dose using pre-estimated values from epidemiological dosimetry models, specifically in this case study. Further experiments in different underground working environments, excluding caves, are needed for more precise observations. It might also be time to update the data regarding the dose contribution from natural radiation sources, as the radon contribution increased according to ICRP.